ПРОЦЕНКА НА ВЛИЈАНИЕТО НА ЈАГ- КАПСУЛОТОМИЈАТА ВРЗ ИНТРАОКУЛАРНИОТ ПРИТИСОК - Наташа Трпевска; Весна Димовска Јорданова (Здружение на офталмолози на Македонија = Macedonian Association of Ophthalmologists, 2014)
Introduction: Nd: YAG laser capsulotomy is relatively a non-invasive procedure which is used as a treatment in patients with posterior capsular opacification (long-term complication after cataract surgery). This complication is seen more in patient after ECCE technique compared to Phaco technique, leading to reduced postoperative visual acuity, glare and primary clouding lens symptoms. Opacification of posterior capsule ”secondary cataract” is caused by increased epithelial cells proliferation, which leads to fibrous changes and posterior capsule opacification, the frequency varies from 8.7% to 33.4%. Design: Retrospective study in a period of 2004-2014 years of 116 eyes Aim: The aim is to assess the influence of YAG-laser capsulotomy on the intraocular pressure in patients with secondary clouding of posterior capsule after cataract surgery. Material and methods: The study included 116 patients with age SD 64 +/- 7 years, who had a cataract intervention with implantation of an artificial intraocular lens. Due to varying degrees of the posterior capsule opacification with the consequent decrease in visual acuity , postoperatively method of Nd: YAG laser capsulotomy or photo disruption was performed. For a period of ten years (2004 - 2014) analysis have been done on the patients, treated by one doctor, providing a single protocol and consistency of results. The effect of the intervention on intraocular pressure (IOP) and the risk factors were analised also. Tonometry on both eyes was performed in each patient pre treatment within the preparation protocol of the patient, and one hour after the intervention. Sixteen of the patients were already diagnosed with glaucoma before the intervention. Results: Changes of the intraocular pressure in the prophylactic treated eyes with topical beta adrenergic agonist were unremarkable compared to the control group where a significant transient increasing of the IOP after a time interval was. The increase in IOP was significantly associated with an interval of 1 hour measurement after the capsulotomy has been performed. Glaucoma patients are more likely to need a long-term IOP control with additional antiglaucomatous drugs than the patients without glaucoma pre-intervention. No correlation was established between the strength of the laser energy and pulse number applied in relation to the intraocular pressure increas
EVALUATION OF YAG CAPSULOTOMY EFFECTS ON THE INTRAOCULAR PRESSURE
Keywords: Posterior capsule opacification (PCO); Nd: YAG laser capsulotomy; Intraocular pressure (IOP); Pseudophakia